Failure in Adult Spinal Deformity Surgery: A Comprehensive Review of Current Rates, Mechanisms, and Prevention Strategies. Issue 19 (1st October 2022) - Burke, John F.; Scheer, Justin K.; Lau, Darryl; Safaee, Michael M.; Lui, Austin; Jha, Sonya; Jedwood, Chloe; Thapar, Isabelle; Belfield, Bethany; Nobahar, Nami; Wang, Albert J.; Wang, Elaina J.; et al.
Abstract : Study Design: Literature review. Objective: The aim of this review is to summarize recent literature on adult spinal deformity (ASD) treatment failure as well as prevention strategies for these failure modes. Summary of Background Data: There is substantial evidence that ASD surgery can provide significant clinical benefits to patients. The volume of ASD surgery is increasing, and significantly more complex procedures are being performed, especially in the aging population with multiple comorbidities. Although there is potential for significant improvements in pain and disability with ASD surgery, these procedures continue to be associated with major complications and even outright failure. Methods: A systematic search of the PubMed database was performed for articles relevant to failure after ASD surgery. Institutional review board approval was not needed. Results: Failure and the potential need for revision surgery generally fall into 1 of 4 well-defined phenotypes: clinical failure, radiographic failure, the need for reoperation, and lack of cost-effectiveness. Revision surgery rates remain relatively high, challenging the overall cost-effectiveness of these procedures. Conclusion: By consolidating the key evidence regarding failure, further research and innovation may be stimulated with the goal of significantly improving the safety and cost-effectiveness of ASD surgery.